Parent characteristics associated with approval of their children drinking alcohol from ages 13 to 16 years: prospective cohort study - Sharmin, S.; Kypri, K.; Wadolowski, M.; Bruno, R.; Khanam, M.; Aiken, A.; Hutchinson, D.; M Najman, J.; Slade, T.; McBride, Nyanda; Attia, J.; P Mattick, R. (Wiley-Blackwell Publishing Asia, 2018)
Objective: We investigated parent sociodemographic and drinking characteristics in relation to whether they approved of their children drinking at ages 13, 14, 15 and 16 years. Methods: We collected data annually from 2010–2014, in which 1,927 parent–child dyads, comprising school students (mean age 12.9 years at baseline) and one of their parents, participated. Our operational definition of parental approval of children drinking was based on the behaviour of parents in pre-specified contexts, reported by children. We measured parents’ drinking with the Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) scale and performed logistic regression to estimate associations between exposures and each wave of outcomes. Results: Parents’ approval of their children's drinking increased from 4.6% at age 13 years to 13% at age 16 years and was more common in parents of daughters than parents of sons (OR 1.62; 95%CI: 1.23 to 2.12). Parents in low-income families (OR 2.67; 1.73 to 4.12), single parents (OR 1.62; 1.17 to 2.25), parents with less than a higher school certificate (OR 1.54; 1.07 to 2.22), and parents who drank more heavily (OR 1.17; 1.09 to 1.25) were more likely to approve of their child drinking. Conclusions: Socially disadvantaged parents were more likely to approve of their children drinking alcohol. Implications for public health: The findings identify high-risk groups in the population and may help explain the socioeconomic gradients in alcohol-related morbidity and mortality seen in many countries.